Ileo-sigmoid knotting presented as a rare cause of intestinal obstruction and bowel ischemia: A case report - Sunil Kumar Yadav; Madan Gopal Vashist; Bhardwaj, Sachin; Kumar, Gaurav; Shukla, Kartikay; Dutta, Sourav Sankar (Asian Journal of Medical Sciences, 2024)
Ileosigmoid knotting causing intestinal obstruction is also known as double volvulus or compound volvulus. It is a rare cause of intestinal obstruction. It involves the sigmoid and ileum causing closed-loop intestinal obstruction. The endoscopic decompression in ileosigmoid knotting may lead to perforation of intestine. We present a case of 80-year-old male patient who presented with ileosigmoid knotting at our surgical emergency setting.